2003
DOI: 10.1093/aje/kwg002
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Risk of Breast Cancer in 10,808 Women: A Cohort Study

Abstract: The authors prospectively investigated the relation between stressful life events and risk of breast cancer among 10,808 women from the Finnish Twin Cohort. Life events and breast cancer risk factors were assessed by self-administered questionnaire in 1981. A national modification of a standardized life event inventory was used, examining accumulation of life events and individual life events and placing emphasis on the 5 years preceding completion of the questionnaire. Through record linkage with the Finnish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
234
6
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(259 citation statements)
references
References 46 publications
6
234
6
13
Order By: Relevance
“…Our results are at variance with the only other prospective cohort study to evaluate the association between stressful life events and subsequent breast cancer risk [24]. This study, of 10,808 women in Finland, based upon 180 cancer cases identified during 15 years of follow-up, concluded that life events were associated with an increased risk of breast cancer-findings that were interpreted as suggesting a role for life events in breast cancer aetiology through hormonal or other mechanisms [24].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our results are at variance with the only other prospective cohort study to evaluate the association between stressful life events and subsequent breast cancer risk [24]. This study, of 10,808 women in Finland, based upon 180 cancer cases identified during 15 years of follow-up, concluded that life events were associated with an increased risk of breast cancer-findings that were interpreted as suggesting a role for life events in breast cancer aetiology through hormonal or other mechanisms [24].…”
Section: Discussioncontrasting
confidence: 51%
“…This study, of 10,808 women in Finland, based upon 180 cancer cases identified during 15 years of follow-up, concluded that life events were associated with an increased risk of breast cancer-findings that were interpreted as suggesting a role for life events in breast cancer aetiology through hormonal or other mechanisms [24]. However, our finding of no association, based upon increased breast cancer endpoint availability, is in agreement with other studies of specific life events (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…We thus analyzed the cohort studies based on 19 items (1,2,3,5,6,7,9,10,11,12,16,17,18,20,21,22,25,26,27) and the case-control studies based on 17 items (1,2,3,5,6,7,10,11,12,16,17,18,20,21,22,25,27). Items 9 and 26 were not used in the evaluation of case-control studies since they contain questions that do not apply to this type of study.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…A positive association between stress and breast cancer was observed in cohort studies 8,9 and some case-control studies 9,10,11,12,13,14,15 , while other case-control studies do not indicate evidence of such an association 16,17 .…”
Section: Introductionmentioning
confidence: 91%
“…Lillberg et al, indicated that a twofold increase in breast cancer risk owing to disruption of marriage, e.g. divorce, separation or death of a spouse, by epidemiological data of 10808 women (Lillberg et al, 2003). Holwerda et al, found that mortality hazard ratio for feeling of loneliness was 1.3 in men, 1.04 in women with a 10-year follow-up of 4,004 older persons (Holwerda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%